Effect of surfactant materials to nanoparticles formation under pulsed plasma conditions and their antibacterial properties. (2018) - Omurzak, E.; Tegin, R. Adil Akai; Kyzy, A. Bekpolot; Satyvaldiev, A.; Zhasnakunov, Z.; Umetova, G.; Kelgenbaeva, Z.; Abdullaeva, Z.; Mashimo, T.
Abstract: Pulsed plasma between two Zn rods submerged into aqueous solution of cetyl trimethylammonium bromide (CTAB) and sodium dodecyl sulphate (SDS) surfactants resulted in formation of pure ZnO nanorods, while the pulsed plasma between two Zn rods in water without surfactant yielded a mixture of ZnO and Zn nanoparticles. Carbon coated ZnO nanorods with about 20 nm thickness and 150 nm length were synthesized by this method using different surfactant materials such as CTAB and SDS. Cu nanoparticles of about 10 nm in size were also synthesized by the pulsed plasma in aqueous solution of 0.2% gelatine as surfactant material. Surfactant materials served as protective and stabilizing agent and induced formation of smaller sized particles with larger surface area, which in turn inhibited excellent antibacterial activity for Escherichia coli ( E.coli ). Silver nanoparticles stabilized by SDS exhibited much higher antibacterial activity against E.coli than that of without surfactant.